Importância do diagnóstico da síndrome metabólica na determinação do risco cardiovascular em pacientes hipertensos - Hirota, Andrea Harumi [UNIFESP] (2008)
We evaluated the significance of a diagnosis of metabolic syndrome (MetS), as defined by the National Cholesterol Education Program (NCEP) and by the International Diabetes Federation (IDF), in the evaluation of cardiovascular risk in hypertensive patients. The patients were evaluated to identify MetS and any history of cardiovascular disease (CVD). This was a cross-sectional study involving 638 patients, of which 202 (31.7%) had diabetes. The prevalence of MetS was 54.7% when the IDF criteria were used, compared with 45.5% when the NCEP criteria were used (p < 0.05). Using either set of criteria, MetS was associated with type 2 diabetes mellitus (T2DM) (NCEP,OR: 6.8; 95% CI: 4.7-10 and IDF, OR: 8.4; 95% CI: 5.4-13; p < 0.05 for both). We found that, regardless of the diagnostic criteria used, MetS correlated significantly with the risk and history of CVD (NCEP, OR: 2.04; 95% CI: 1.2-3.4; p < 0.05; and IDF, OR: 2.68; 95% CI: 1.5-4.8; p < 0.05), partially caused by the inclusion of patients with diabetes in the sample. In patients without diabetes, MetS diagnosed using the IDF criteria alone was associated with a history of CVD (OR: 2.4; 95% CI: 1.1-5.2; p = 0.029 vs. NCEP criteria, OR: 1.99; 95% CI: 0.9-4.3, p = NS). In patients with T2DM, MetS was not associated with CVD, regardless of the criteria used. We conclude that, among individuals without diabetes, an IDF criteria-based diagnosis of MetS is useful in identifying those at greater risk for cardiovascular disease. Among patients with diabetes, a diagnosis of MetS, regardless of the criteria used, is of little utility in assessing cardiovascular risk. However, a diagnosis of MetS, using either set of criteria, is useful for identifying individuals more likely to develop T2DM.